Not Another Bias Workshop: Using Equity Analytics to Promote Antiracist Teaching. Issue 4 (24th June 2022) - Reinholz, Daniel L.; Reid, Aileen; Shah, Niral
In Short: Meaningful change towards antiracist practices take time. There are no quick fixes. Quick workshops on implicit bias and microaggressions rarely lead to lasting changes in teaching practices. Equity QUantified In Participation (EQUIP) learning communities organize faculty members to work together to promote antiracist teaching. Participation in EQUIP learning communities results in lasting, meaningful changes to both faculty beliefs and practices.